Diversity and Phenetic Relationship of Mountain Papaya (Vasconcellea Pubescens) in Dieng Plateau Based on Morphological Marker - Rifqi, Muhammad Said; Chasani, Abdul Razaq (Journal of Tropical Biodiversity and Biotechnology, 2024)
Vasconcellea pubescens A. DC., commonly referred to as mountain papaya, belongs to the Caricaceae family and is native to the Andean highlands.  In Indonesia, mountain papaya can be found on the Dieng Plateau and has become one of the typical processed products from the Dieng area. The aim of the study is to explore the diversity and phenetic relationship of mountain papaya from the Dieng Plateau based on morphological markers. This study is important to provide information in guiding future conservation efforts. 18 samples were collected from three areas with different altitudes in the Dieng Plateau. In addition, it proved valuable results by elucidating patterns of variation, enabling the identification of distinct groups. A total of 18 samples were collected from three areas with varying altitudes in the Dieng Plateau. Morphological analysis used 22 characters with The Clustering Analysis Method, Principal Component Analysis (PCA), and Diversity Analysis using Multivariate Statistical Package (MVSP) software version 3.1A. The results of cluster analysis showed that mountain papaya accessions were grouped into two main clusters and five sub-clusters. Cluster grouping based on sex distribution characters, flower stalk length, and inflorescence density; there is no grouping based on geographical location or altitude. The Shannon's Index Value (H') for mountain papaya shows moderate phenetic diversity. This suggests that the mountain papaya community remains stable within its substrate and its environmental parameters.